Book review of Léon Krier’s "Albert Speer. Architecture 1932–1942" - Younés, Samir (Journal of Architecture and Urbanism, 2014)
Book review of Léon Krier’s "Albert Speer. Architecture 1932–1942". Journal of Architecture and Urbanism, 38(3), p. 210-212.